2021
DOI: 10.1523/jneurosci.1993-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Coding Strength of Object Identity and Nonidentity Features in Human Occipito-Temporal Cortex and Convolutional Neural Networks

Abstract: A visual object is characterized by multiple visual features, including its identity, position and size. Despite the usefulness of identity and nonidentity features in vision and their joint coding throughout the primate ventral visual processing pathway, they have so far been studied relatively independently. Here in both female and male human participants, the coding of identity and nonidentity features was examined together across the human ventral visual pathway. The nonidentity features tested included tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 69 publications
(113 reference statements)
0
33
0
Order By: Relevance
“…In addition, DNNs often act in surprising non-human-like ways, such as being fooled by adversarial images (Szegedy et al, 2013;Dujmović et al, 2020) and make bizarre classification errors to familiar objects in unusual poses (Kauderer-Abrams, 2017;Gong et al, 2014;Chen et al, 2017). Furthermore, recent work by Xu and Vaziri-Pashkam (2021) failed to find strong neural correlates on high level visual areas when DNNs' internal representation were compared to fMRI data of human participants.…”
Section: Neural Network As a Model Of The Human Visual Systemmentioning
confidence: 98%
“…In addition, DNNs often act in surprising non-human-like ways, such as being fooled by adversarial images (Szegedy et al, 2013;Dujmović et al, 2020) and make bizarre classification errors to familiar objects in unusual poses (Kauderer-Abrams, 2017;Gong et al, 2014;Chen et al, 2017). Furthermore, recent work by Xu and Vaziri-Pashkam (2021) failed to find strong neural correlates on high level visual areas when DNNs' internal representation were compared to fMRI data of human participants.…”
Section: Neural Network As a Model Of The Human Visual Systemmentioning
confidence: 98%
“…We believe that this is due to their reliance of Euclidean distance which underestimated the degree of scale invariance and subsequently (since the transformations were aggregated) the strength of all invariances. Also Xu and Vaziri-Pashkam (2021) found inconsistent embeddings across classes of translated objects, which we believe to be due to the different training setup they employed. We expand on this in the Supplementary Material.…”
Section: Discussionmentioning
confidence: 91%
“…The layers were also chosen in such a manner as to sample the network as evenly as possible, and to at least roughly equate the number of layers extracted from each network. In a control analysis, we found that our sampled layers capture the overall processing trajectory of the network and that the trajectory does not change with the types of layers sampled, as long as they are adjacent to each other in the processing pipeline (S1 Fig) . Although fully-connected layers (including the classification layer) differ from early layers in the network in that they do not follow a weight-sharing constraint over space, past work has found that they encode not just information about object category membership, but also information about features such as shape, position, spatial frequency, and size [19,36], making it appropriate to examine how they jointly encode the features of shape and color at the end of CNN visual processing.…”
Section: Resultsmentioning
confidence: 99%
“…A priori, one would assume that the final fully connected layer encodes object category orthogonally to color, since it is trained to output category labels. However, prior work has shown that fully connected layers encode not just information about object category membership, but also information about features such as shape, position, spatial frequency, and size [ 19 , 36 ]. The present results further show that there is both a significant amount of color representation and a greater amount of color and form interaction in the final compared to the first sampled layer, with the amount of interaction steadily increasing during the course of visual processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation